아동양육시설에 종사하는 생활지도원의 구강건강인지 및 지각요인과 구강건강증진행위에 대한 조사 - 임선아; 송애희; 이명선; Lim, Sun-A; Song, Ae-Hee; Lee, Myeong-Seon (Han'guk Ch'iwisaeng Hakhoe chi, 2012)
Objectives : The aim of this study was to examine the level of oral health knowledge, oral health importance, oral health status and oral health interest of the social workers engaged in child care facilities to analyze the influential factors on oral health promotion activities and provide the basic data for oral health promotion activities. Methods : The subjects in this study were those social workers engaged in child care facilities from May 15th to May 25th in 2011. The self-report questionnaires were distributed and withdrawn and then a total of 205 papers from the subjects that participated in this study were analyzed for the final analysis. Results : 1. Oral health knowledge had $12.16{±}1.66$ in a full score of 15 and oral health importance, oral health status and oral health interest were $1.12{±}0.36$, $2.80{±}0.50$ and $2.14{±}0.8$ respectively in a full score of 5. 2. According to the general characteristics, the difference analysis of cognition-recognition factors showed that singles had significantly higher oral health knowledge married couples (p<0.05) and the social workers unusing auxiliary oral hygiene devices had significantly higher oral health interest than those using them(p<0.01). 3. The mean of oral health promotion was $3.28{±}0.51$, characteristics of detailed specific-area were as follows ; the toothbrushing was $3.77{±}0.57$, the use of fluoride was $2.67{±}0.98$, periodic dental screening and treatment were $2.98{±}1.09$ and eating habits was $4.14{±}0.57$. These results generally showed tooth-brushing and eating habits show a little higher figures. 4. Considering the factors oral health promotion behaviors of social workers engaged in child care facilities, the higher oral health interest was, the higher oral health promotion behavior was. Conclusions : It seems that social workers engaged in child care facilities are required to pay attention to the importance of oral health and learn oral health knowledge, which will lead to much better improvement of oral health for children brought up by them.